2013
DOI: 10.1167/13.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural effects on the assumed light source direction: Evidence from English and Hebrew readers

Abstract: When judging the 3D shape of a shaded image, observers generally assume that the light source is placed above and to the left. This leftward bias has been attributed to experiential factors shaped by the observers' handedness or hemispheric dominance. Others have found that experiential factors can rapidly modify the direction of the assumed light source, suggesting a role for learning in shaping perceptual expectations. In the current study, instead, we assessed the contribution of cultural factors affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(70 citation statements)
references
References 34 publications
10
59
1
Order By: Relevance
“…As they claimed, both left- and right-handed observers show this tendency, but it is more pronounced among the right-handers. However, in agreement with subsequent studies (Mamassian & Goutcher, 2001; McManus, Buckman, & Woolley, 2004), a recent study failed to associate this orientation effect with handedness; instead, it demonstrated that cultural factors, such as scanning habits, can affect the way visual scenes are inspected and organized in determining the assumed light source direction (Andrews, Aisenberg, d’Avossa, & Sapir, 2013). Perhaps, as Proulx (2014) has precisely suggested, the perception of shape from shading may not be always necessarily based on a hard-wired internal representation of lighting direction; rather, it assesses the direction of lighting in the scene adaptively.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…As they claimed, both left- and right-handed observers show this tendency, but it is more pronounced among the right-handers. However, in agreement with subsequent studies (Mamassian & Goutcher, 2001; McManus, Buckman, & Woolley, 2004), a recent study failed to associate this orientation effect with handedness; instead, it demonstrated that cultural factors, such as scanning habits, can affect the way visual scenes are inspected and organized in determining the assumed light source direction (Andrews, Aisenberg, d’Avossa, & Sapir, 2013). Perhaps, as Proulx (2014) has precisely suggested, the perception of shape from shading may not be always necessarily based on a hard-wired internal representation of lighting direction; rather, it assesses the direction of lighting in the scene adaptively.…”
Section: Introductionsupporting
confidence: 64%
“…As discussed earlier in this review, some studies showed that the degree of preference for a top-left lighting condition in a 3D shape perception can be determined by handedness (Sun & Perona, 1998) whereas other studies claimed that this can be determined by cultural factors (e.g., reading direction), rather than handedness (Andrews et al, 2013). Ocklenburg and Güntürkün, 2009) demonstrated that the direction of head-turning in human adults can be associated with handedness or footedness (e.g., Ocklenburg & Güntürkün, 2009) whereas Shaki (2013) found that this can be shaped by cultural spatial habits, such as reading direction.…”
Section: A Dynamic Model For the Origins Of Directionality Biases mentioning
confidence: 91%
“…We used a task that had previously shown subtle differences between groups whose long-term (cultural) experience of reading direction differed (Andrews et al, 2012), suggesting that it should have been possible to detect differences based on long-term experience between our groups if they were in fact present.…”
Section: Discussionmentioning
confidence: 99%
“…Following Andrews et al (2012), the relation between the proportion of convex judgments (“no” judgments in our game) and stimulus orientation was estimated for each participant using a multivariate logistic regression:p(C|θ)=1/(1+e-f(θ)]),where for a given stimulus direction θ , f ( θ ) was a series of sine and cosine functions,f(θ)=α0+α1cosθ+β1sinθ.…”
Section: Methodsmentioning
confidence: 99%
“…When interpreting the shape of ambiguous 3D surfaces the visual system exhibits a bias that directional illumination is mostly from above (Ramachandran, 1988; Sun and Perona, 1996a,b, 1998; Mamassian and Goutcher, 2001; Stone et al, 2009; de Montalembert et al, 2010; Morgenstern et al, 2011; Schofield et al, 2011; Andrews et al, 2013) and slightly from the left (Sun and Perona, 1998; Mamassian and Goutcher, 2001; Mamassian et al, 2003; McManus et al, 2004; Thomas et al, 2008; de Montalembert et al, 2010; Andrews et al, 2013). The light-from-above bias is well illustrated by experiments demonstrating that discs with top-dark luminance gradients are seen as concavities while those with top-bright luminance gradients are perceived as convexities (Ramachandran, 1988).…”
Section: Introductionmentioning
confidence: 99%